Soil hydrological properties and conditions, site preparation, and the long-term performance of planted Scots pine (Pinus sylvestris L.) on upland forest sites in Finnish Lapland. - Mäkitalo, Kari (Dissertationes Forestales)
Dissertation. University of Helsinki, Faculty of Agriculture and Forestry, Department of Forest Ecology. 2009